Reflection on Adult Education Policy Development and Implementation in Tanzania since Independence: Emerging Issues and Lessons - Bhalalusesa, Eustella (Papers in Education and Development, 2021)
This paper intends to reflect on the adult education policy development and implementation in Tanzania since independence in 1961, especially from the period of launching the Arusha Declaration in 1967. This period serves to be a very significant milestone in adult education because of the policies and programmes that were conceived, developed and implemented. The paper is a product of desk study and the reflection is done using a historical approach. In this context, writing using the historical perspective of adult education in Tanzania is important because it enables us to understand the past and how different key players may have acted on the basis of prevailing beliefs and ideologies to influence the present situation and to avoid drawing misleading conclusions. One notable observation is that the absence of an independent unit to coordinate adult education activities at the national level coupled with lack of reliable data and research proven information have greatly affected the present status of adult education sub-sector. Keywords: adult education, policy development, programme implementation